Distinct effect of preconditioning with p38 MAPK signals on matrix-expanded human synovium-derived stem cell chondrogenesis: sb203580 favors chondrogenic differentiation while anisomycin benefits endochondral bone formation - Zhang, Ying; Pei, Ming; Lv, Chaoliang (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCartilage defects are often accompanied by inflammation, presenting a major challenge in clinical treatment. Adult stem cells offer a promising approach for cartilage regeneration; however, in vitro expansion leads to replicative senescence, hindering their application. Our previous studies have demonstrated that decellularized extracellular matrix (dECM) can serve as an in vitro “microenvironment” to promote stem cell expansion and chondrogenic potential. In this study, we hypothesized that pretreatment with p38 mitogen-activated protein kinase (MAPK), a key pathway driving inflammation, would impair chondrogenesis in dECM-expanded adult stem cells.MethodsHuman synovium-derived stem cells (SDSCs) were expanded for one passage on either dECM or plastic culture flasks and pretreated with p38 MAPK, followed by chondrogenic or osteogenic induction.ResultsWe found that pretreatment with sb203580, a p38 MAPK inhibitor, enhanced chondrogenic differentiation of dECM-expanded SDSCs, whereas pretreatment with anisomycin, a p38 MAPK activator, favored both chondrogenic hypertrophy and osteogenic differentiation of dECM-expanded SDSCs. In SDSC pretreatment, p38 MAPK significantly upregulated the non-canonical Wnt signaling pathway during dECM expansion and chondrogenic induction. The significant upregulation of Wnt5a induced by anisomycin combined with dECM expansion may indicate the highest osteogenic potential; SDSC pretreatment with sb203580 combined with dECM expansion exhibited the strongest chondrogenic differentiation and the highest levels of Wnt11.DiscussionThis study suggests that p38 MAPK pretreatment may play a key role in dECM-expanded tissue-specific stem cell-mediated cartilage regeneration. Further verification of Wnt-related regenerative mechanisms remains to be determined.